The Antibacterial Activities of the Extracts Isolated from the Aruda Leaf (Ruta angustifolia) Digested in Polar, Semipolar, and Nonpolar Solvents - Windy Taebenu; Febri O. Nitbani; Hermania E. Wogo (Journal of Applied Chemical Science, 2013)
A research has been done to know content of metabolit sekunder and antibacterial activity of polar, semipolar and nonpolar extract aruda leaf (Ruta angustifolia). Aruda leaf extract obtained with method of maceration, while antibacterial activity test carried out by the method of dilution and diffusion agar method against Escherichia coli (gram negative) and Staphylococcus aureus (gram positive). Metabolit sekunder of content implied in aruda leaf (Ceiba pentandra) that is triterpenoid, flavonoid, saponin, polifenol, tanin and alkaloid. The result of research with dilution method that methanol extract have rate value pursue minimum (KHM) equal 20% for the bacterium Escherichia coli of and not have rate value pursue minimum (KHM) for the Staphylococcus aureus bacteria. Ethyl acetate extract have rate value pursue minimum (KHM) equal to 10% of Escherichia Coli and not have of Staphylococcus aureus bacteria, while petroleum ether extract have not rate value pursue minimum (KHM) for the Escherichia Coli bacteria and for the Staphylococcus aureus bacteria. The results showed that the diffusion method with methanol extract have inhibition diameter of bacteria Escherichia coli and Staphylococcus aureus is 1,97 mm and 1,8 mm. Ethyl acetate extract average inhibition diameter is 2,33 mm in the Escherichia coli bacteria and the Staphylococcus aureus bacteria is 1.93 mm while the petroleum ether extract average inhibiton diameter 1,6 mm in Staphylococcus aureus bacteria and of inhibition diameter against the Escherichia Coli bacteria is 1,73 mm.